PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN DANA OTONOMI KHUSUS TERHADAP BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI ACEH - Muhammad Iqbal; Tarmizi Abbas; Ratna Ratna (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to examine the effect of Own Source Revenues, General Allocation Funds, Special Allocation Funds, and Special Autonomy Funds on Regional Expenditures. This study uses a combination of cross section data with time series in 23 regencies/cities in Aceh Province during 2010-2017, obtained from the Budget Realization Report (LRA) issued by the Directorate General of Regional Financial Management of the Ministry of Finance (DJPK Ministry of Finance). The data analysis method used is Panel Data Regression with the help of Eviews 10. The results of this study prove that Own Source Revenues, General Allocation Funds, Special Allocation Funds, and Special Autonomy Funds have a positive and significant effect on regional expenditures. The magnitude of the effect of Own Source Revenues, General Allocation Funds, Special Allocation Funds, and Special Autonomy Funds on regional expenditure is 94.22% and the remaining 5.78% is influenced by other variables outside this research model. It is recommended to local governments to use Own Source Revenues, General Allocation Funds, Special Allocation Funds, and Special Autonomy Funds effectively and efficiently so that Regional Expenditures can be increased, and the Special Autonomy Fund should be used in the interests of the general public so as to reduce poverty and the people of Aceh become more prosperous. Keywords:   Own Source Revenues, General Allocation Funds, Special Allocation Funds, Special Autonomy Funds, Regional expenditures.